2022
DOI: 10.5658/wood.2022.50.4.272
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Essential Oils from Citrus × natsudaidai (Yu. Tanaka) Hayata Peels at Different Ripening Stage

Abstract: The essential oil extracted from Citrus × natsudaidai (Yu. Tanaka) Hayata peels is known to have various biological properties. However, the chemical composition of essential oil is influenced by the ripening stages of fruits, which then affects related biological activities. This study investigates the antioxidant activities of essential oils extracted from Citrus × natsudaidai peels at different ripening stages (immature, mature, and overripe). The essential oils were extracted using the hydro-distillation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Plants contain a wide variety of constituent compounds, many of which exhibit antibacterial (Ham et al, 2020), antifungal (Adfa et al, 2020;Jang et al, 2012;Lee et al, 2021;Yoon and Kim, 2023), anti-inflammatory (Myeong et al, 2023;Yang et al, 2019), and antioxidant effects (Lee et al, 2021;Nam et al, 2018;Yang et al, 2022). Coicis Semen, the seeds of the Coix lacryma-jobi plant, is a traditional medicinal herb commonly used in East Asian countries such as China, Japan, and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Plants contain a wide variety of constituent compounds, many of which exhibit antibacterial (Ham et al, 2020), antifungal (Adfa et al, 2020;Jang et al, 2012;Lee et al, 2021;Yoon and Kim, 2023), anti-inflammatory (Myeong et al, 2023;Yang et al, 2019), and antioxidant effects (Lee et al, 2021;Nam et al, 2018;Yang et al, 2022). Coicis Semen, the seeds of the Coix lacryma-jobi plant, is a traditional medicinal herb commonly used in East Asian countries such as China, Japan, and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported the potential biological activity of extracts soluble in various polar solvents (i.e. methanol, ethanol, and distilled water) from several species such as Azadirachta excelsa seeds and Guibourtia tessmanii bark for anti-termite (Adfa et al, 2023;Ella Nkogo et al, 2022), herbal plants of Phellodendri cortex, Magnoliae cortex and some plants for antifungi (Na and Kim, 2022;Yoon and Kim, 2023), 12 herbal plants for antimicrobial resistance (Ham and Kim, 2022), Quercus gilva and Citrus × natsudaidai for antioxidant activity (Huh et al, 2022;Yang et al, 2022a) and the Lauraceae family for anti-asthmatic activity (Yang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…enterocolitica. Plant natural products, including forest products, contain compounds with various biological functions (Adfa et al, 2020;Ahn et al, 2021;Arsyad et al, 2020;Ham and Kim, 2019;Huh et al, 2022;Lee et al, 2021;Na and Kim, 2022;Nkogo et al, 2022;Oramahi et al, 2022;Yang et al, 2022;Yoon and Kim, 2021). The library of extracts used in this study is a collection of extracts of plants that include forest products that are used as foods or herbal medicines, and since they are natural materials, they are considered to be safe.…”
Section: Introductionmentioning
confidence: 99%